ONLINE CULTURE DURING THE COVID-19 PANDEMIC - Hayati Nupus (Universitas Galuh, 2021)
The virus of the COVID-19 pandemic has caused the government to apply stay-at-home rules, to anticipate the spread of the Novel Corona Virus which is increasingly spreading through human social activities. The COVID-19 pandemic has changed all forms of human life, including educational learning at the formal level of higher education, students are required to learn from home using technology in the form of visualization of networks in the form of technology such as laptops or mobile phones, so that learning and activities can be seen directly shown and carried out through internet network from home, without having to touch physical such as face-to-face or other social routines. The existence of this COVID-19 pandemic forces the public to be responsive to technology, towards a new culture, where communication and routines can be done such as online learning for students at home, communication, new culture, and digital culture will be the implications of this online learning process, with online learning activities. During a pandemic, new experiences with technology, without being able to physically explore yourself and with your family at home, so at least until this COVID-19 Pandemic ends. A basic element of this changing social system is the behavior of individuals and groups in and between systems. Ultimately, the success of online learning is determined by the adaptation of these students to new cultures, new experiences, and technologies as environmental behavioral implications.Keywords: Online learning, Culture, COVID-19 Pandemic